FIELD RESEARCH OF AGRICULTURAL AIR VEHICLE CHEMICAL EQUIPMENT - Vitaly V. Dudnik; Andrey S. Kopkin; Andrey S. Gurinov (Advanced Engineering Research, 2011)
Methods and results of the experimentation on the particle-size determination essential in calculating drops concretion are offered. Drop dispersivity under low-volume spraying is specified by the analysis methods of traces negatives. Calculations and checking of distribution density of fluid particles dropped  by MI-2 helicopter have been done under adverse and cross wind.